2020
DOI: 10.1002/eng2.12274
|View full text |Cite
|
Sign up to set email alerts
|

Virtual microstructure design for steels using generative adversarial networks

Abstract: The prediction of macro‐scale materials properties from microstructures, and vice versa, should be a key part in modeling quantitative microstructure‐physical property relationships. It would be helpful if the microstructural input and output were in the form of visual images rather than parameterized descriptors. However, only a typical supervised learning technique would be insufficient to build up a model with real‐image‐output. A generative adversarial network (GAN) is required to treat visual images as ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Their cGAN uses an augmented loss based on the matching of perimeter, volume, and Euler characteristics. DGM studies in microstructure design have also used other advanced image translation methods introduced in computer vision such as super-resolution [59], CycleGAN [68,8], and Pix2Pix [68,127].…”
Section: Microstructure Nanostructure and Metamaterialsmentioning
confidence: 99%
“…Their cGAN uses an augmented loss based on the matching of perimeter, volume, and Euler characteristics. DGM studies in microstructure design have also used other advanced image translation methods introduced in computer vision such as super-resolution [59], CycleGAN [68,8], and Pix2Pix [68,127].…”
Section: Microstructure Nanostructure and Metamaterialsmentioning
confidence: 99%
“…Lee et al [94] employed DCGAN [134], CycleGAN [197] and Pix2Pix [70] to generate realistic virtual microstructural graph images. KL-divergence, a similarity metric that is considerably below 0.1, confirmed the similarity between the GAN-generated and ground truth images.…”
Section: Dan Et Al Proposed Matganmentioning
confidence: 99%
“…The quality of the GAN generated designs was confirmed by FEM simulation and experimental evaluation, demonstrating that GANs are capable of generating metaporous material designs with satisfactory broadband absorption performance. Applications in Material Science GAN models Micro and crystal structure generation and design Hybrid (WGAN-GP [52]+GIN) [148], GAN+GP-Hedge Bayesian optimization framework [181], CrystalGAN [123], Composition-Conditioned Crystal GAN [85] Designing complex architectured materials GAN-based model [112] Inorganic materials design MatGAN [27], WGAN [7] based model [65] Virtual microstructure design (DCGAN [134], CycleGAN [197] and Pix2Pix [70]) [94] Topological design of metaporous materials for sound absorption GAN based model [188] 4.8 Finance Financial data modeling is a challenging problem as there are complex statistical properties and dynamic stochastic factors behind the process. Many financial data are time-series data, such as real property price and stock market index.…”
Section: Dan Et Al Proposed Matganmentioning
confidence: 99%
“…Iyer et al [16] demonstrated that microstructure can be generated from process conditions using an auxiliary classifier Wasserstein generative adversarial network (WGAN). Lee et al [17] used scanning electron microscope (SEM) and optical microscope (OM) images of various metal surfaces for GAN algorithm learning to create realistic virtual microstructures, which can be used to study the relationship between microstructures and physical properties. For flow stress prediction, Shouwu et al [18] reported that flow stress can be accurately predicted through an artificial neural network (ANN) by comparing the accuracy of the ANN model and the Arrhenius model.…”
Section: Introductionmentioning
confidence: 99%